Prognostic value of diabetes and metformin use in a real-life population of head and neck cancer patients - De Falco, Vincenzo; Vitale, Pasquale; Brancati, Christian; Cicero, Giuseppe; Auriemma, Annunziata; Addeo, Raffaele (Frontiers in Medicine, 2023)
Head and neck carcinoma (HNC) is a disease with a poor prognosis despite currently available treatments. The management of patients with this tumor is often complicated by several comorbidities. Among these, diabetes is the second most frequent and its influence on the prognosis is not known. In this work, we collected data on progression free survival (PFS) and overall survival (OS) of one hundred twenty-three patients with HNC who received biweekly cetuximab maintenance treatment after first-line chemotherapy. We then compared the survival of nondiabetic patients versus that of diabetics’ one. Surprisingly, both PFS (4 vs 5 months, HR 2.297, p<0.0001) and OS (7 vs 10 months, HR 3.138, p<0.0001) were in favor of diabetic patients, even after excluding other clinical confounding factors. In addition, we also studied survivals in patients taking metformin, a widely used oral antidiabetic drug that has demonstrated antitumor efficacy in some cancers. Indeed, diabetic patients taking metformin had better PFS and OS than those not taking it, 7 vs 5 months (HR 0.56, p=0.0187) and 11 vs 8.5 months (HR 0.53, p=0.0170), respectively. In conclusion, real-world outcomes of biweekly cetuximab maintenance remain comparable to clinical trials. The prognostic role of diabetes and metformin was confirmed to be significant in our series, but further prospective studies are needed for a definitive evaluation.